ANALISIS PERGERAKAN KERETA REL LISTRIK UNTUK DISAIN SISTEM KESELAMATAN KERETA API OTOMATIS = ANALYSIS OF ELECTRIC RAIL TRAIN MOVEMENTS FOR AUTOMATIC TRAIN PROTECTION SYSTEM DESIGN - Kamar, Syamsul (BPPT, 2015)
Abstract Result of research suggest that the cause of train accident in Indonesia is dominated by human error in the form of indiscipline road users, the absence of a doorstop at some railroad tracks, and negligence of the drivers. To minimize the train crash as a result of these matters, in particular due to errors of commuterline machinist in Jakarta-Bogor-Depok-Tangerang-Bekasi (Jabodetabek), it is required to consider use of the